Self-assembled chiral photonic crystals from a colloidal helix racemate - Lei, Qun-li (2020)
Chiral crystals consisting of microhelices have many optical properties, while presently available fabrication processes limit their large-scale applications in photonic devices. Here, by using a simplified simulation method, we investigate a bottom-up self-assembly route to build up helical crystals from the smectic monolayer of a colloidal helix racemate. With increasing the density, the system undergoes an entropy-driven cocrystallization by forming crystals of various symmetries with different helical shapes. In particular, we identify two crystals of helices arranged in binary honeycomb and square lattices, which are essentially composed of two sets of opposite-handed chiral crystals. Photonic calculations show that these chiral structures can have large complete photonic band gaps. In addition, in the self-assembled chiral square crystal, we also find dual polarization band gaps that selectively forbid the propagation of circularly polarized light of a specific handedness along the helical axis direction. The self-assembly process in our proposed system is robust, suggesting possibilities of using chiral colloids to assemble photonic metamaterials.